Perancangan Aplikasi Pembelajaran Steganografi Algoritma Least Signification Bit Dengan Metode Computer Assisted Intruction - Gulo, Aperius Frediks (LPPM UNIKA Santo Thomas Medan, 2017)
Steganography which is an art and technique that can be used to do digital data security or the process of hiding secret messages in the form of text in other forms so that it is not easily known by others. Least Significant Bit (LSB) is one of the steganography methods that is used to insert or hide messages by replacing rows of rear bits. From the classroom observations it was revealed that generally pay attention when the teacher explains the subject matter and gives practice questions. But communication in the classroom generally occurs in one direction which is dominated by the teacher or tutor. This theory learning often makes students bored when compared to practical activities that are directly carried out at the computer or with other technological tools. By applying the Computer Assisted Intruction (CAI) learning model, it uses strategic learning methods by providing material, training and games that greatly assist the process of delivering material by the instructor. Mobile-based Least Significant Bit (LSB) Algorithm Learning Application using adobe flash CS6, can be an alternative learning method. To overcome these problems and see the ownership of smartphones in Indonesia is almost evenly shared by students and the community. Then this application can support these learning activities